2017
DOI: 10.5334/labphon.99
|View full text |Cite
|
Sign up to set email alerts
|

Talker and background noise specificity in spoken word recognition memory

Abstract: Prior research has demonstrated that listeners are sensitive to changes in the indexical (talker-specific) characteristics of speech input, suggesting that these signal-intrinsic features are integrally encoded in memory for spoken words. Given that listeners frequently must contend with concurrent environmental noise, to what extent do they also encode signal-extrinsic details? Native English listeners' explicit memory for spoken English monosyllabic and disyllabic words was assessed as a function of consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…The present study is the first study that investigated talker familiarity benefit in recognition memory and word identification for words spoken in a non-native language, and the role of background noise and non-native proficiency on this talker familiarity effect. After successfully learning to recognize four previously unfamiliar talkers over the course of four days, the familiar talker benefit in nonnative listening was observed for recognition memory in line with other studies for native (Bradlow & Pisoni, 1999;Cooper & Bradlow, 2017;Goh, 2005;Goldinger, 1996;Luce & Lyons, 1998;Palmeri et al, 1993;Sheffert, 1998) and non-native listening (Trofimovich, 2005;Winters et al, 2013). At the same time, no talker familiarity benefit was observed during non-native word identification in 2 Following Levi et al (2011) and Nygaard and Pisoni (1998), a second analysis was conducted including voice recognition performance on the last training day as a potential predictor of relative progress.…”
Section: The Role Of Talker Familiarity In Recognition Memory and Worsupporting
confidence: 87%
See 2 more Smart Citations
“…The present study is the first study that investigated talker familiarity benefit in recognition memory and word identification for words spoken in a non-native language, and the role of background noise and non-native proficiency on this talker familiarity effect. After successfully learning to recognize four previously unfamiliar talkers over the course of four days, the familiar talker benefit in nonnative listening was observed for recognition memory in line with other studies for native (Bradlow & Pisoni, 1999;Cooper & Bradlow, 2017;Goh, 2005;Goldinger, 1996;Luce & Lyons, 1998;Palmeri et al, 1993;Sheffert, 1998) and non-native listening (Trofimovich, 2005;Winters et al, 2013). At the same time, no talker familiarity benefit was observed during non-native word identification in 2 Following Levi et al (2011) and Nygaard and Pisoni (1998), a second analysis was conducted including voice recognition performance on the last training day as a potential predictor of relative progress.…”
Section: The Role Of Talker Familiarity In Recognition Memory and Worsupporting
confidence: 87%
“…The discrepancies in the emergence of the effect of indexical information in these two different types of tasks have been previously observed by Luce and Lyons (1998), Kittredge et al (2006), and Lee and Zhang (2015), who found the effect of indexical information in a recognition memory task and repetition priming, but not in a lexical decision task and during semantic priming. While the recognition memory task requires minimal contact with the mental lexicon and does not abstract away indexical information in spoken words (Cooper & Bradlow, 2017), the word identification task focuses on sound and lexical processing which does abstract from voice-specific characteristics (Cutler et al, 2010a, b). Indeed, even listeners not familiar with a language demonstrate effects of indexical information in recognition memory (Winters et al, 2013) but not in word identification (Levi et al, 2011).…”
Section: The Role Of Talker Familiarity In Recognition Memory and Wormentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the aforementioned studies start with an initial encoding phase, during which participants are presented with a series of word stimuli. During the second phase of the experiment, participants are presented with a mix of new and old (i.e., previously presented) words and are asked to indicate whether each stimulus is new or old, and/or whether the voice in which it is spoken is the same or not (Bradlow, Nygaard, & Pisoni, 1999;Cooper & Bradlow, 2017;Palmeri, Goldinger, & Pisoni, 1993). Other studies have used more implicit measures of processing, such as word identification in noise (Goldinger, 1996;González & McLennan, 2007) and lexical decision (Luce & Lyons, 1998).…”
Section: Abstractionist Versus Episodic Views Of the Mental Lexiconmentioning
confidence: 99%
“…These studies indicate that extra-phonological information is encoded in some form along with phonological information. Interestingly, such information may not be limited to talker-specific information (Goldinger, 1998;Luce, McLennan, & Charles-Luce, 2012; McLennan & Luce, 2005;Vitevitch & Donoso, 2011), but may also include other aspects of the auditory context in which a word was encountered, such as background noise (Cooper & Bradlow, 2017;Pufahl & Samuel, 2014).…”
Section: Abstractionist Versus Episodic Views Of the Mental Lexiconmentioning
confidence: 99%